The Value of Operational Flexibility in the Presence of Input and Output Price Uncertainties with Oil Refining Applications - Dong, Lingxiu; Kouvelis, Panos; Wu, Xiaole (Management Science, 2014)
Refining is indispensable to almost every natural-resource-based commodity industry. It involves a series of complex processes that transform inputs with a wide range of quality characteristics into refined finished products sold to end markets. In this paper, we take the perspective of a profit-maximizing refiner that considers upgrading its existing simple refinery to include intermediate-conversion flexibility, i.e., the capability of converting heavy intermediate components to light ones. We present a stylized two-stage stochastic programming model of a petroleum refinery to investigate the value drivers of conversion flexibility and the impact of input and output market conditions on its economic potential. Conversion flexibility adds value to refineries by either transforming a nonprofitable situation into a profitable one (referred to as purchase benefit) or improving profitability of an already profitable situation (referred to as unit revenue benefit). In a real-data-calibrated numerical study, we find the value of conversion flexibility (VoC) to be significant, accounting for 40% of the expected profit with conversion, and the purchase benefit and unit revenue benefit are equally important. Contrary to the intuition that, as a recourse action, conversion offers higher value for greater input price volatility, we find that VoC may decrease in input price volatility as a result of the differential impacts of increasing price volatility on the purchase benefit and the unit revenue benefit. Refineries also vary in their range flexibility, i.e., the ability to accommodate a narrow or wide range of inputs of different quality levels. Whether the range flexibility increases or decreases the value of conversion flexibility is affected by the direction in which the refinery expands its processing range and the heaviness of crude oils. This paper was accepted by Martin Lariviere, operations management.